Protective roles of melatonin regulated mitochondrial DNA methylation and respiratory metabolism in ram sperm cryopreservation - Hu, Hai; Liu, Liming; Wang, Keqiang; Bao, Jingjing; Zhao, Zengyuan; Zhong, Rongzhen; Xu, Shangrong; Fang, Yi (Frontiers in Veterinary Science, 2025)
Mitochondrial dysfunction, especially compromised respiratory metabolism, is a serious obstacle of sperm cryopreservation. This study aims to determine the effect of melatonin supplement on respiratory metabolism of frozen-thawed ram sperm. Semen was slowly frozen with or without melatonin supplement, while fresh semen was used as a control. The results showed that melatonin clearly improved ATP production, oxygen consumption and respiratory chain complex activities, while it decreased reactive oxygen species and nitrite concentrations in frozen-thawed sperm (p < 0.05). Consequently, the viability, motility and fertility of frozen-thawed sperm were also recovered by melatonin. Strikingly, promoter methylation levels of several key mitochondrial respiratory chain genes were dramatically increased along with decreased expression levels in frozen-thawed sperm, which can be partially repaired by melatonin supplement (p < 0.05). This might be attributed to the expression change of mtDNMT1 among three groups (p < 0.05). Furthermore, the declined expression of MTNR1A and MTNR1B were found in frozen-thawed sperm (p < 0.05). The treatment of melatonin receptor antagonist indicated that MTNR1A could have a key role in the regulation of melatonin on mitochondrial function of frozen-thawed sperm. Collectively, these findings provide a new perspective on the epigenetic regulation of sperm cryopreservation.